A study of the temperature variation effect in a steel sample for rapid analysis using LIBS. (March 2022) - Lin, Jingjun; Yang, Jiangfei; Huang, Yutao; Lin, Xiaomei
Highlights: The temperature effect of plasma spectrum in steel samples analyzed by LIBS was studied. It is found that the spectral intensity of ions and atoms increases with the increase of temperature. When the temperature rises to the melting point (1432 °C), the spectral intensity tends to be stable. Abstract: The relationship between a sample's temperature and the plasma spectrum is of great significance for the quality of smelting. In this work, the main purpose was to study the temperature variation effect of the plasma spectrum in a steel sample for on line analysis using LIBS. Both the spectral intensity of ions and atoms increased as the temperature increased. When the temperature rises to the melting points (1432 °C), the spectral intensity tends to stabilize. To analyze the reasons for the enhancement of spectral lines, the plasma temperature was calculated by the Boltzmann plane method; and the plasma temperature at 1432 °C and 20 °C was 14, 709 K and 14, 227 K, respectively. The results showed that the sample temperature had little effect on the plasma temperature. Compared with 20 °C, the correlation coefficient of Cr II 205.56 nm, Mn II 293.31 nm, Si I 288.16 nm and C I 193.09 nm at 1432 °C increased from 0.9577, 0.9516, 0.9681, and 0.9739 to 0.9832, 0.9947, 0.9925, and 0.9912, respectively. The RMSEP of the four elements at 1432 °C also increased from 1.24%, 0.49%, 0.85%, and 0.41% to 0.27%, 0.09%, 0.16%, and 0.08%, respectively. The LOD of the four elements reached 128 ppm, 135 ppm, 78 ppm, and 65 ppm at 1432 °C, respectively. It indicated that on-line monitoring of molten steel can be realized by controlling the temperature in the field smelting process.